ACCOUNTING FOR PRODUCTION AND SALE OF PRODUCTS IN ENTERPRISES - N.Sh.Esanmurodova; I.B.Sapayev; Sh.Sh.Dehqonboyev; A.O.Muxammadolimov; O.I.Ortikov; N.S.Qo’chqorboyeva; D.R.Omonov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
It is necessary to take into account the impact of the global financial crisis in determining the current and prospective measures of the social and economic development of our country, to formulate economic development programs in terms of the impact of these events, and to implement them consistently. "The world financial economic crisis, ways and measures to eliminate it in the conditions of Uzbekistan" are given a wide and detailed description.